Landscapes from the bee perspective: an application of SolBeePop to field study data - Schmolke, Amelie; Galic, Nika; Hinarejos, Silvia (Food and Ecological Systems Modelling Journal, 2025)
Introduction : The temporal and spatial pattern of floral resources in a landscape is an important driver of dynamics of pollinator species, such as solitary bees. Thus, the representation of complex landscapes in models is of interest when assessing whether landscapes could provide sufficient resources to sustain populations of solitary bee species. The consideration of landscape compositions is also important when estimating exposures to pesticides and their potential effects on managed and natural populations. At the same time, information on the use of complex landscapes by solitary bees is lacking for most species. This challenges the inclusion of this important aspect into models representing bee species and model applications for risk assessment and management. Methods : In the current paper, we tested options to include different levels of information available to represent compositions of agricultural landscapes. We applied the population model for solitary bees, SolBeePop, to simulate untreated control trials from field studies conducted with Osmia bicornis , compared model outputs to study data and assessed model performance using different scenarios. First, we reviewed literature reporting pollen compositions of bee-collected brood provisions for O. bicornis . As studies were conducted in a range of different landscapes and geographical regions, generalised floral preferences of the species could be derived. Results : In aggregating land-cover information using increasingly detailed information, we showed that the consideration of multiple resources across the landscape and study period improved the model performance in representing the field study data. At the same time, we demonstrated that simplified, conservative scenarios can be generated and evaluated with the model if information is lacking on species’ preferences as well as resource distributions in time and space. Conclusions and relevance : The representation of complex landscapes using different levels of detail makes SolBeePop a flexible tool for simulating solitary bee populations in agricultural landscapes using often limited information, thereby supporting ecological risk assessment and management.